2022
DOI: 10.1177/11786302221123576
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Potential Intermediate Host Snails of Urogenital Schistosomiasis, Human Water Contact Behavior and Water Physico-chemical Characteristics in Alwero Dam Reservoir, Ethiopia

Abstract: Introduction: Urogenital schistosomiasis is one of public health problems in lowland areas of Ethiopia. The disease is caused by Schistosoma haematobium. Freshwater Bulinus snails are intermediate hosts for the parasite transmission. The aim of the study was to assess intermediate host snails of urogenital schistosomiasis, human water contact behavior and physico-chemical characteristics of Alwero Dam reservoir. Methods: Bulinus snails were sampled from 12 sites of Alwero Dam. Bulinus snails were collected, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…30 Similarly, a previous study conducted near Alwero Dam reported that males tended to have more frequent contact with freshwater than females. 29 Age, occupation, and infection history were also factors that influenced participants knowledge, perception, and risky or safe practices in the research region, consistent with previous studies. 23 , 28 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…30 Similarly, a previous study conducted near Alwero Dam reported that males tended to have more frequent contact with freshwater than females. 29 Age, occupation, and infection history were also factors that influenced participants knowledge, perception, and risky or safe practices in the research region, consistent with previous studies. 23 , 28 …”
Section: Discussionsupporting
confidence: 88%
“…Even though our data showed the community’s primary drinking water sources are public hand pumps, for other essential activities such as washing, bathing and recreational purposes such as swimming and playing, the community relies on dam/river water, as previously reported. 29 Additionally, a considerable number of participants frequently practice open-air urination and defecation, which could lead to the persistence of schistosomiasis in the area. Hence, it is imperative to develop integrated control strategies to break the transmission cycle effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of cercarial infection was 33%, which is higher than the estimates in in Ethiopian rift valley regions, where the prevalence of infection was 30.5% [ 37 ]. This infection prevalence can be underestimated as the natural cercariae shedding method cannot detect snail prepatent infection rates [ 38 , 39 ]. Lymnea natalensis shed three types of cercariae and contributed to 61.4% of the total infection.…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, in the Tiko focus, the Bulinus snail species was abundant on rocky than sandy or muddy substratum habitat type. Rocky substratum habitat preference by Bulinus snails provide adhere to resist the water wave action thereby avoiding dislodgment [ 60 ]. The rocky biotope has other ecological advantages as it increases films of mud and fine salts that cover these rocks and favours aquatic plant growth which is used as a food source for snails [ 23 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, in the Tiko focus, the Bulinus snail species was abundant on rocky than sandy or muddy substratum habitat type. Rocky substratum habitat preference by Bulinus snails provide adhere to resist the water wave action thereby avoiding dislodgment [60]. The rocky biotope has other ecological…”
Section: Plos Onementioning
confidence: 99%